The Concept of Ta'dib Al-Attas and Its Relevance to the Implementation of the ISMUBA Curriculum - Sani, Akbar; Achadi, Muh Wasith (TA'DIBUNA: Jurnal Pendidikan Agama Islam, 2025)
This study aims to conduct an in-depth analysis of the concept of ta’dib in the thought of Syed Muhammad Naquib al-Attas and to explore its relevance to the implementation of the ISMUBA curriculum. The main focus of this research is to explain how the Islamic educational principles proposed by al-Attas can serve as a normative framework for reviewing the ISMUBA curriculum. This study adopts a qualitative approach through a literature review and descriptive analysis method. The data sources include the original works of Syed Muhammad Naquib al-Attas, official ISMUBA curriculum documents, and scholarly articles on ISMUBA curriculum implementation obtained from Google Scholar. The findings reveal that the implementation of the ISMUBA curriculum reflects the core principles of ta’dib as articulated by Syed Muhammad Naquib al-Attas, particularly in its emphasis on the integration of knowledge (‘ilm), action (‘amal), and ethics (adab) within the educational process. The ISMUBA curriculum not only targets cognitive achievement but is deliberately designed to shape students' character and spirituality through a holistic and integrative approach. Nevertheless, practical challenges such as limited teacher training and inadequate infrastructural support remain significant obstacles that need to be addressed. This research can serve as a reference for curriculum developers and Muhammadiyah education practitioners in designing instructional strategies oriented toward the cultivation of noble character.